Comorbidity of attention deficit hyperactivity disorder in young adults who had major depressive disorder - Merve Yazıcı; Meltem Puşuroğlu (Annals of Saudi Medicine)
BACKGROUND: The comorbidity of Major Depressive Disorder (MDD) and Attention Deficit Hyperactivity Disorder (ADHD) in adults is well recognized. The role of ADHD in the etiology of MDD, as well as the overlap of genetic and environmental factors between these two disorders, is an area of research. ADHD symptoms are considered risk factors for MDD. OBJECTIVES: The study aimed to examine the relationship between MDD in young adults with history of ADHD. DESIGN: Retrospective and observational study SETTINGS: Outpatient clinic of a tertiary hospital PATIENTS AND METHODS: Data of young adults diagnosed with MDD, aged 18–25 years and seen between January 2017 and May 2023, were included. Individuals with comorbidities other than ADHD in adulthood were excluded from the study. The sociodemographic and clinical data of a total of 489 cases, as well as data on childhood psychiatric referrals, diagnoses, and treatment histories, were retrospectively examined. MAIN OUTCOME MEASURES: ADHD diagnosis history and clinical impact in adults diagnosed with MDD SAMPLE SIZE: 489 RESULTS: A total of 489 cases (68.9% female) with a mean age of 21.14 years were included in the study. It was determined that 8% of the cases had ADHD in adulthood, 13.3% in childhood, and 31.9% had at least one mental health diagnosis during childhood. The rate of ADHD diagnosis was significantly higher in males than females in both adulthood and childhood. Additionally, the age of diagnosis of MDD was lower in individuals with ADHD diagnosis and/or those who have discontinued ADHD treatment. CONCLUSIONS: In young adults diagnosed with MDD, the comorbidity of ADHD should also be considered. It is important to acknowledge that ADHD is not just a childhood disorder but a lifelong disorder due to its negative consequences, and to develop appropriate strategies in this regard. LIMITATİONS: Retrospective observational design and the single-center setting, which may affect the generalizability of the findings.